BERPIKIR KREATIF DALAM PENGAMBILAN KEPUTUSAN - Eko Handoyo, Heri Rohayuningsih, (Faculty of Social Science, Universitas Negeri Semarang, 2015)
Everyone is always faced with the choice to take a decision. To be able to take the right decisions, every person should know the steps. This paper presents what the decision-making steps and what is the importance of creative thinking in decision making.Creative thinking will help decision makers to improve the quality and effectiveness of problem solving and decision making results were made. In relation to the process of decision making, creative thinking is needed, especially in identifying problems and develop alternative solutions.